Gender-sensitive Architecture: Assessing Space Qualities and Perceptions in Housing Design - Saragih, Marcelina; Kusuma, Hanson Endra; Purwaningrum, Rr. Diah Asih (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
Housing designs should not only consider aspects of form and function but should also pay attention to gender perspectives. This study aims to examine the influence of gender perspectives on the architectural design of residential housing. Employing a mixed method of a qualitative approach and a questionnaire-based online survey, this research explores user perceptions and preferences in applying gender-sensitive approaches to housing design. The findings reveal that gender-sensitive approaches are highly preferred in housing designs, with a particular emphasis on accommodating the inhabitants’ needs. The approach effectively addresses the specific needs of masculine and feminine individuals as inhabitants, which can significantly improve the quality of life within the house. This research emphasizes the urge to incorporate a gender perspective as one of the design considerations to create inclusive houses that are responsive to the needs of individuals of diverse genders.